2019
DOI: 10.1038/s41467-019-08303-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity landscape of the honey bee gut microbiota

Abstract: The structure and distribution of genomic diversity in natural microbial communities is largely unexplored. Here, we used shotgun metagenomics to assess the diversity of the honey bee gut microbiota, a community consisting of few bacterial phylotypes. Our results show that most phylotypes are composed of sequence-discrete populations, which co-exist in individual bees and show age-specific abundance profiles. In contrast, strains present within these sequence-discrete populations were found to segregate into i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
273
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(305 citation statements)
references
References 54 publications
30
273
2
Order By: Relevance
“…For example, multiple strains of a sulfur-oxidizing endosymbiont were found to co-colonize individual hosts of deep-sea mussels, presumably because they encode complementary functions [4, 5]. In contrast, strains of the human gut microbiota have been shown to segregate among individuals, resulting in host-specific genetic profiles [68]. However, despite the increased awareness of the existence and functional importance of strain-level diversity in host-associated bacterial communities, little is known about differences in diversity across host species, or the underlying mechanisms which constrain and maintain diversity within and among hosts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, multiple strains of a sulfur-oxidizing endosymbiont were found to co-colonize individual hosts of deep-sea mussels, presumably because they encode complementary functions [4, 5]. In contrast, strains of the human gut microbiota have been shown to segregate among individuals, resulting in host-specific genetic profiles [68]. However, despite the increased awareness of the existence and functional importance of strain-level diversity in host-associated bacterial communities, little is known about differences in diversity across host species, or the underlying mechanisms which constrain and maintain diversity within and among hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous studies on bacterial isolates have demonstrated an impressive amount of genomic diversity within phylotypes, where strains isolated from different hosts often represent divergent phylogenetic sub-lineages [1417]. Moreover, a recent metagenomic analysis of the gut microbiota of the Western honey bee, Apis mellifera, found that even within the same host species divergent sub-lineages can be present [6]. We refer to these sub-lineages as sequence-discrete populations (SDPs), since metagenomic data demonstrated that they were discrete from each other [6], in addition to being sufficiently divergent to be considered as different bacterial species [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…microbiome of vertebrates (Schloissnig et al, 2013;Garud and Pollard, 2020) and invertebrates (Ellegaard and Engel, 2019), marine bacteria (Delmont et al, 2019;Salazar et al, 2019) or crustaceans (Madoui et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Geographic isolation of individual hosts over the host life span would then lead to genetic isolation of the symbiont populations and to symbiont population structure. Genomic variation and genetic isolation have been observed for horizontally transmitted symbionts of the human gut microbiome 19 and of the honey bee gut microbiome 20 . Moreover, structured symbiont populations can also emerge within an individual host, as observed for Vibrio fischeri colonizing the squid light organ, where different light organ crypts are infected by a specific strain 21 .…”
mentioning
confidence: 99%